Impacts of Deforestation on Soil Quality and Water Resources in Tropical Forest Areas of Sumatra - Dwi Syamsih (PT. Anagata Sembagi Education, 2024)
Deforestation poses a significant threat to the tropical forest regions of Sumatra, impacting soil quality and water resources crucial for ecosystem health and human well-being. This paper synthesizes the multifaceted impacts of deforestation on soil and water in Sumatra and proposes strategies for sustainable land management. Deforestation leads to a decline in soil organic matter, nutrient levels, and microbial diversity, affecting soil fertility and erosion susceptibility. Additionally, the loss of forest cover disrupts the hydrological cycle, altering water availability, quality, and distribution. Increased surface runoff and sedimentation degrade water bodies, threatening aquatic biodiversity and community water supplies. Integrated analysis highlights the interdependencies between land cover change, soil degradation, and hydrological processes, emphasizing the need for holistic management approaches. Reforestation, agroforestry, and community engagement are proposed as essential strategies for mitigating deforestation impacts and promoting ecosystem resilience in Sumatra.